Synthesis and Antitumor activity of N1-(3-Pyridoyl)- 3-Methyl-4-(Substituted Azo) Pyrazol-5-Ones - P. Singh, C.; Singh, Archana (Asian Journal of Chemistry, 2010)
A series of N1-(3-pyridoy)-3-methyl-4-(substituted azo) pyrazol-5-ones have been synthesised by the reaction of substituted azo ethyl-3-oxobutyrates with 3-pyridoylhydrazine, using glacial acetic acid as condensing agent. All compounds were evaluated against the Lymphoid leukemia L-1210 tumor system in mice. Some of them showed significant antitumor activity.